Self Help Group: An Effective Approach for Empowerment of Women - Lakhwinder Kaur , R. K. Kalra; R.K.Dhaliwal (Indian Journal of Extension Education, 2014)
The present study focussed on the economic, social and managerial impacts of self help groups on empowering women. The study was conducted in three cultural zones of Punjab. A sample of 200 members of self help groups belonging to these zones were the respondents of the study. An interview schedule was used to document the impact of self help groups. The findings of the study clearly revealed economic empowerment of rural women. The economic benefits gained from enrolling in the groups were ’higher price of their products instead of selling individually’ (91%) and ’understood banking operations to avail credit facility’ (81.50%). A large number of women in Punjab developed ’courage to think independently’ (99.50%), ’understood group activities’ (96%) and ’managed group activities’ (95.50%) after joining the group. Furthermore the social empowerment of the members in terms of team spirit (97%), talking freely within family (94%), confidence in dealing with people (95.50%) were enhanced. It indicates that self help groups bring economic upliftment, leadership skills in managing the group and inculcate great confidence in the members of selected groups to succeed in their day to day life.